Evaluation of the coaches educators training implementation of the PAPA project: A comparison between Norway and France - Van Hoye, A.; Larsen, T.; Sovik, M.; Wold, B.; Heuze, J.-P.; Samdal, O.; Ommundsen, Y.; Sarrazin, P. (Scandinavian Journal of Medicine & Science in Sports, 2015)
This study cross-culturally compares the implementation process of the Empowering Coaching™ training program to grassroots coaches (GCs) by trained Coach Educators (CEs) from the Promoting Adolescent Physical Activity project in Norway and France. This program targets children's health through coach training to create a more positive environment. Using the RE-AIM framework, indicators of implementation processes at staff level were defined for adoption, implementation, and maintenance. CEs (n = 18) were interviewed about their professional use of the training, and video-filmed delivering the intervention trial workshops. GCs (n = 185) responded to a questionnaire after the workshops. Results showed that CEs were keen to participate in this project (16/18; 89%), to stay involved (12/16; 75%), and to diffuse the principles after the research project (12/12; 100%). CE training seemed effective as results indicated that CEs applied the principles of the program during the workshops and covered a high degree of the content (78%). Cross-cultural differences were found as the French Football Federation CE dropped out of the program, as Norwegian CEs delivered the content with higher fidelity and had higher enjoyment and pace scores than French CEs. More indicators are needed to use the RE-AIM framework for cross-cultural comparison.